A bi-objective optimization model for tactical planning in the pome fruit industry supply chain - Catala, Luis Pedro (2016)
In this work, a multi-period mixed integer linear programming formulation for the medium-term planning of the apples and pears supply chain is presented. Given the supply chain structure, demand data, and harvesting dates, the proposed approach integrates production, processing, distribution, and inventory decisions considering two conflicting objectives: profit and product supply shortage. The mathematical model is solved by using the lexicographic method to deal with the multi-objective optimization. The system is analyzed in the face of changes in storage, processing and transportation capacities. Major results indicate that in order to minimize supply shortage (leading objective) in the second part of the season, beneficial trade opportunities have to be missed along the year with the consequent reduction in the total profit (subordinated objective). To illustrate the approach, a pome fruit industry located in the “Alto Valle de Río Negro y Neuquén” Argentine region is considered as a case study.